The psychological experience of women who survived HELLP syndrome in Cape Town, South Africa - Rizwana Roomaney; Michelle G. Andipatin; Anika Naidoo (AOSIS, 2014)
Background: Haemolysis, elevated liver enzymes and low platelet count (HELLP syndrome) is a high-risk pregnancy condition that could be fatal to mother and/or baby. It is characterised, as the acronym indicates, by haemolysis, elevated liver enzymes and low blood platelets. Objective: This study explored women in Cape Town's psychological experience of HELLP syndrome. Method: Six participants who previously experienced HELLP syndrome were interviewed. Using a grounded theory approach, themes emerged and a model illlustrating the psychological experience of HELLP syndrome was constructed. Results: The major themes that emerged were the perceived lack of information, a need to assign blame and a shift in focus. Themes of not knowing and trance and/or surreal experience underpin the cognitive aspects of the HELLP syndrome experience. Themes that expressed feelings of an inability to control, whirlwind and/or rapid pace and support acted together to bind the experience. Finally, emotions such as anger, ambivalence, disbelief, anxiety, guilt, loneliness and fear were present throughout the experience. Conclusion: This study developed an initial exploratory model representing the psychological experience of HELLP syndrome in a sample of South African women. Underlying this entire experience was a perceived lack of information which had a profound effect on numerous aspects of the experience ranging from where to locate blame to the varied emotions experienced.   Agtergrond: Die HELLP sindroom is 'n hoë-risiko swangerskap toestand wat kan dodelik vir moeder en/of baba wees. Dit word gekenmerk deur hemolise, verhoogde lewerensieme en lae bloedplaatjies. Doelwit: Hierdie studie het Suid-Afrikaanse vroue se sielkundige ervaring van die HELLP sindroom ondersoek. Metode: Ses deelnemers wat voorheen HELLP sindroom ervaar het is ondervra. Met die gebuik van gefundeerde teorie as 'n teoretiese raamwerk en ontleding het temas na vore gekom en 'n model wat die sielkundige ervaring van HELLP sindroom illustreer, is gebou. Resultate: Die vernaamste temas wat na vore gekom het was die oënskynlike gebrek aan inligting, 'n behoefte om skuld toe te skryf en 'n verskuiwing in fokus. Die tema van nie weet en beswyming en/of surrealistiese ervaring ondersteun die kognitiewe aspekte van die HELLP sindroom. Temas wat gevoelens van geen beheer, warrelwind en/of vinnige tempo en ondersteuning uitgesprek het, het saam opgetree om die ervaring te bind. Ten slotte, emosies soos woede, teenstrydigheid, ongeloof, angs, skuldgevoelens, eensaamheid en vrees was teenwoordig in die hele ervaring. Gevolgtrekking: Hierdie studie het van'n aanvanklike ondersoekende model van die sielkundige ervaring van HELLP sindroom tot 'n steekproef van die Suid-Afrikaanse vroue ontwikkel. Onderliggend aan hierdie hele ervaring was 'n oënskynlike gebrek aan inligting wat 'n diepgaande uitwerking gehad het op talle aspekte van die ervaring wat gewissel het van waar om die blaam te plaas tot die uiteenlopende ervaarde emosies.